1999
DOI: 10.1076/phbi.37.1.63.6317
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Triterpenoids Isolated from Lantana camara

Abstract: The known triterpenoids lantic acid, camaric acid, camarinic acid and lantanilic acid were isolated from Lantana camara (L.) cultivated in Egypt. The antibacterial activity of lantic acid was carried out using bioautography assays for Gram-positive and Gramnegative bacteria. Lantic acid was found to possess strong antibacterial activity against Escherichia coli and Bacillus cereus, in which 0.08 and 0.1 g were the minimum inhibition doses, respectively, compared to 0.05 and 0.005 g for chloramphenicol, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 6 publications
0
13
0
1
Order By: Relevance
“…The antibacterial activity of lantic acid (57) isolated from L. camara leaves was studied in Grampositive and Gram-negative bacteria using bioautography assays (Saleh et al, 1999). Lantic acid was found to possess strong antibacterial activity against E. coli and Bacillus cereus, in which 0.08 and 0.1 µg were the minimum inhibitory doses, respectively, compared to 0.05 and 0.005 µg for chloramphenicol, respectively.…”
Section: Antibacterial Antifungal Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…The antibacterial activity of lantic acid (57) isolated from L. camara leaves was studied in Grampositive and Gram-negative bacteria using bioautography assays (Saleh et al, 1999). Lantic acid was found to possess strong antibacterial activity against E. coli and Bacillus cereus, in which 0.08 and 0.1 µg were the minimum inhibitory doses, respectively, compared to 0.05 and 0.005 µg for chloramphenicol, respectively.…”
Section: Antibacterial Antifungal Activitymentioning
confidence: 99%
“…camara (roots) Pan et al (1993b) hederagenin (20), 25-hydroxy-3-oxoolean-12-en-28-oic acid (21) Singh et al (1996) 21,22β-epoxy-3β-hydroxyolean-12-en-28-oic methyl ester (22) Misra & Laatsch (2000) camarin (23), lantanone (24) L. camara (leaves) Begum et al (2006Begum et al ( , 2008b 22β-tigloyloxylantanolic acid (25) camarilic acid (26) L. camara (aerial parts) Begum et al (1995) L. camara (roots) Misra & Laatsch (2000) 19α-hydroxy ursolic (42), lantaiursolic acid (43) Pan et al (1993b) ursonic acid (44) L. camara (aerial parts) Begum et al (1995) lantacin (45) Begum et al (2006Begum et al ( , 2008b Singh et al (1990) 24-hydroxy-3-oxours-12-en-28-oic acid (48) L. trifolia (leaves) Rwangabo et al (1988) 3,24-dioxo-urs-12-en-28-oic acid (49) L. camara (leaves) Yadav & Tripathi (2003) α-amyrin (50) L. camara (leaves, flowers and stems) Ahmed et al (1972a;1972b) methyl 3-oxours-late (51) L. camara (leaves) Barua et al (1969) methyl-24-hydroxy-3-oxoursolate (52) L. indica (aerial parts) Singh et al (1989a) camaranoic acid (53) L. camara (aerial parts) Begum et al (2008a) lantoic acid (54) Begum et al (2008b); Roy & Barua (1985) camarinic acid (55) L. camara (leaves, 1 stems 2 ) Siddiqui et al (1995) 1 ; Barre et al (1997) 1 ; Saleh et al (1999) …”
Section: Triterpenoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Years after this work, more studies have been conducted on 1 and 2, and they refer to Siddiqui's article for spectral assignments. [6][7][8][9][10][11][12][13][14][15][16] However, our analysis indicated that eight signals were wrongly assigned.…”
Section: Resultsmentioning
confidence: 99%
“…Test extract was obtained from L. camara which is a notorious and poisonous weed [25] imposing serious threat to native vegetation and biodiversity [26]. Though L. camara has been screened for its antimicrobial activities [27][28][29] but work with dermatophytes has not been done as yet. It is the first study which evaluates in vitro as well as in vivo (mice model) antidermatophytic potency of L. camara.…”
Section: Discussionmentioning
confidence: 99%